ANALISIS PUISI “AKU” KARYA CHAIRIL ANWAR DENGAN PENDEKATAN EKSPRESIF SEBAGAI PENDIDIKAN KARAKTER - Jimmy Maulana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
A work in the form of writing, one of which is a poem, contains a great meaning from the author.The work is made based on the taste of an author who wants to share something worthy. One of the problems faced by readers is a lack of knowledge of the relationship between a work and its author. So that it can produce character values that can be imitated by readers.This research aims to (1) describe Chairil Anwar's relationship with the poem "AKU" to find character education for his work and (2) describe the background of Chairil Anwar in writing a poem entitled "AKU". This paper is analyzed using a qualitative descriptive method. The poem "AKU" by Chairil Anwar was analyzed through data collection steps, (1) reading the author's biography; (2) to analyze the inspiration and purpose of the author in making a poem entitled "AKU" to find the value of education and to describe it.After analyzing the work of analyzing, one can pay attention to the reasons and goals of the author in making a literary work in the form of a poem entitled "AKU", after knowing the reasons and goals of Chairil Anwar's poem "AKU" to show such things, we can get to know more specifically an author who has a special background in making a work he makes.As a result we can learn the background of the author to help the reader to explore the knowledge about the relationship between the character of a writer and his work as well as to provide knowledge for readers to find out the purpose of making the work so that what the writer wants to convey is conveyed so that it can be a positive role model for students in particular.